Endometriosis, hormonal therapy and oncological risks - A.M. Grigorenko (Publishing House TRILIST, 2021)
Endometriosis is now considered as benign disease. However, a correlation was found between endometriosis and several types of cancer. Endometriomas are found in 17-44% of patients with endometriosis and can be frequent precursors of ovarian cancer (endometrioid and clear cell ovarian tumors are more common). This process can be realized through several mechanisms: predominance of certain cytokines, oxidative stress and local hyperestrogenia, genetic mutations including PTEN, PIK3CA, ARID1A, Wnt/β-catenin, microsatellite instability, Src and KRAS. There are no generally accepted approaches to non-invasive early diagnosis of ovarian cancer, especially in borderline tumors and early stages of malignancy. The lack of accurate screening programs for ovarian cancer emphasizes the importance of identifying high-risk, moderate-risk, and low-risk groups. Screening is not recommended in the general population in the low-risk group. Annual CA125 evaluation and transvaginal pelvic ultrasound with general and special gynecological examination are recommended in the moderate-risk group in postmenopause. Transvaginal ultrasound of the pelvic organs with CA125 evaluation is performed every 6 months in the high-risk group, starting from 30 years or 5-10 years before the youngest age of ovarian cancer onset in relatives. The main method of diagnosing tumors is expert ultrasound of the pelvic organs (simultaneously with transabdominal ultrasound). The main tumor markers are CA125 (single evaluation has low diagnostic value), risk malignancy index (RMI) and HE4. Clinical trials are going on and various methods of prevention, screening and treatment of these diseases are being developed. Probably, dienogest can help to solve the problem. Existing results of research are promising, but insufficient since they show both the positive effects of progestin therapy and minor cases of cancer detection during therapy that are not related to the use of progestins, but probably indicate unknown mechanisms of transformation in endometriosis.